IMPLEMENTASI METODE TALAQQI PADA PEMBELAJARAN TAHFIDZUL QURâ€™AN DI SMP IT NURUL AZMI MEDAN - Munawir Pasaribu; Ika Puspita (Cattleya Darmaya Fortuna, 2022)
This research is entitled â€œImplementation Of The Talaqqi Method in LearningTahfidz Qurâ€™an at SMP IT Nurul Azmi Medanâ€. This study aims to determine the implementation of teachers in tahfidz learning with the talaqqi method, describe the design of tahfidz learning in carrying out the learning process for students, and the benefits of implementing the talaqqi method in tahfidz learning. The approach used in this research is a qualitative approach with a descriptive type of research. Data collection technique is to use observation, interviews and documentation at the school.